(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2013)
The philosophical problem of the abuse of judicial power, as present in the Brazilian reality, since its formation, has generated a historic legal legitimacy crisis in our society. The abuse of power committed by the regulatory authority, when it ignores the law, that it should respect, can encourage the emergence of subversive reactions of subjects. We will examine the topic through the film Black God, White Devil and the study of philosophical theories that relate law, power and communication.